Nilai-Nilai Pendidikan Islam dalam Al-Qur’an Surah Al-Kahfi Ayat 66-82 - Haryati, Mita; Razzaq, Abdur; Imron, Kristina (LPPM Institut Pendidikan Nusantara Global, 2024)
This article discusses the values of Islamic education contained in the Al-Qur'an surah Al-Kahf verses 66-82, Islamic education is a teaching and learning process that is carried out consciously and is based on the Al-Qur'an and Hadith with the aim that the object The goal of education is being able to achieve goals that are in accordance with the concept of Islamic teachings. However, the phenomenon that is occurring in the world of education today is a reflection of the decline in students' manners towards teachers. This can be seen by the large number of students who do not have good manners in speaking, behaving and dressing which is not in accordance with the concept of Islamic teachings, all of which shows that morals, morals and manners are very worrying. This research aims to be a reference for students to be able to adopt the values of Islamic education so that people are able to emulate the lessons in the stories of Prophet Musa and Prophet Khidir. This research is literature research with a descriptive-analytical approach, namely relating to the analysis of interpretations of the values of Islamic education in the Al-Qur'an surah Al-Kahf verses 66-82. The results of this research show that the values of Islamic education contained in Surah Al-Kahf verses 66-82 include curiosity, humility, patience, respect for teachers, admitting mistakes and apologizing, sincerity, critical thinking and helping. These values are contained in every story passed by Prophet Musa and Prophet Khidir.